Communicating mathematical ideas in a digital writing environment: the impacts on mathematical reasoning for students with and without learning disabilities - Huscroft-D’Angelo, Jacqueline; Higgins, Kristina; Crawford, Lindy (Social Welfare: Interdisciplinary Approach, 2014)
Mathematical reasoning is often underdeveloped in students with learning disabilities (LD). Problem solving and reasoning represent one of the most important aspects of a mathematics curriculum. The purpose of the present study was to examine how communication through writing in mathematics via a digital environment impacts the mathematical reasoning of students with and without LD. Specifically, the research was guided by research questions: (1) What differences exist between the mathematical reasoning of students with and without LD prior to and after using a digital writing environment? (2) How does use of the digital writing environment differ between students with and without LD? (3) To what extent does student reasoning change overtime when emphasis is placed on communication via writing in mathematics? Oral reading and math fact fluency as well as participants’ working memory were used as academic variables. The Math Reasoning Inventory (MRI; Burns, 2012) is a formative assessment designed to evaluate mathematical reasoning through a face-to-face interview. The primary focus is on core numerical reasoning strategies and understanding. Subjects participated in an intervention focused on communication in mathematics through the use of digital writing tools in a computer-based mathematics program. Results reveal that communication through writing or peer-based discussions around mathematics can impact students’ reasoning skills. Reasoning is a fundamental skill in mathematics and remains an area in which students with LD continuously struggle; therefore, interventions focused on advancing student reasoning will be increasingly pivotal to mathematics education. Students in this study showed improvement in different areas of reasoning over the course of the intervention and responded differently to the types of writing environments that were offered. Regardless of which digital environment was preferred by students with and without LD, results demonstrated that incorporating writing into mathematics to communicate mathematical information benefited all students in this study and has the potential to impact mathematics education.
Keywords: mathematical reasoning; students with or without LD; digital environment